Qualidade no atendimento ao cliente: um estudo na academia Israel Fitness na cidade de Parintins-AM - Melo, Thiago Tavares (Brasil, 2024)
The business market is competitive and requires continuous changes by organizations. In pursuit of service quality, managers face the challenge of preparing their team for this market. This research describes the formal process on quality in customer service based on a bibliographical research that analyzes the main issues involved on the theme quality of service. The research is characterized as a case study and was carried out through the application of a questionnaire with the clients of the company Israel Fitness and its general objective is to investigate the degree of satisfaction of the clients of the Israel Fitness gym regarding the quality of the service. To achieve this general objective, the following specific objectives were proposed: to identify, in the literature, which parameters to measure the quality of customer service; verify the profile of the company's customers; show the level of customer satisfaction. The conclusions seek to analyze the environment of the Israel Fitness academy, in addition to describing the aspects and data that prove the quality of service provided by employees to their customers, applying theory to practice. Finally, some considerations are made about the quality of care.